Strategic Role of Early Childhood Development (ECD) Teacher in Parenting Education - Lies Zakaria; Vindya Anjar Pramesti (SEAMEO CECCEP, 2023)
Considering the time spent in early childhood development centre vs. at home – parents/caregivers play bigger role in optimizing children’s growth and development. Ironically, upon entering school, parents were as if “handing over the responsibility” to teachers – considered to be more knowledgeable. Additionally, interaction between teachers and parents was cold, insufficient to do problem solving together, moreover sharing about good parenting practice.This project has been implemented in 3 districts (Bogor, West Lombok, and East Lombok) in Indonesia, involving 120 teachers and 60 school leaders from rural/suburb areas. During the project period, more than 250 parenting sessions were held, with average attendance of 40 parents per session. Most teachers agreed that the project has been helpful in building their understanding of early childhood development, and skills in interacting with children and parents. Most parents admitted that the session was educational and fun. The distinctive features of this project are: First, focus on family instead of child/service. Most teachers’ training focused on curriculum and pedagogy, overlooking family/parenting. Secondly, the andragogy approach, using adult education principles, which includes active participation in discussions, games, and problem solving. This is unlike the conventional one-direction communication and lacking dialogue. Third, introduction of play as part of facilitation methods in parenting class, to help parents realize about fun-learning concept.